SEBK-İ HİNDÎ ŞAİRLERİNİN (NÂİLÎ, NEŞÂTÎ, FEHÎM, ŞEHRÎ VE ŞEYH GÂLİB) KASİDELERİNDE ÖVME VE ÖVÜNME - BAYKUT, HAKAN (Fırat Üniveristesi, 2010)
Kaside, klasik Türk edebiyatında genellikle belirli kişileri övmek için şairlerin tercih ettikleri bir nazım şeklidir. Bu çalışmada ?Sebk-i Hindî? adıyla bilinen klasik edebiyat döneminin önemli şairlerinden Fehîm-i Kadîm, Nâilî-i Kadîm, Neşâtî, Şehrî ve Şeyh Gâlib'in kasidelerindeki övme ve övünme beyitleri incelenmiştir. Beyitler, övülen kişilere göre sınıflandırılmış ve genel olarak karşılaştırma yapılmıştır. Amaç, adı geçen şairlerin övmeyi ve övünmeyi nasıl yaptıklarını, kimleri övdüklerini detayıyla tespit edebilmektir.Çalışmamızda amaçlanan hedeflere genel olarak ulaşılmış ve şairlerin kimleri övdükleri, nasıl övdükleri, şiirleri incelenip tasnif edildikten sonra gözler önüne serilmiştir. Şairler genel olarak Osmanlı Devleti'nin siyasi ve kültürel ortamına uygun olarak kendilerini maddi ve manevi olarak koruyacakları kişileri övmüşlerdir. Bunlar en başta hükümdarlar ve yüksek rütbeli devlet adamlarıdır. Ardından mensup oldukları tarikatların şeyhlerini (Mevlana) veya İslam dininin tanınmış şahsiyetlerini ( Hz. Ali, Hz. Ebubekir, Hz. Hüseyin vs.) övmüşlerdir.Kendilerini överken de genellikle diğer şairlerden üstünlüklerini ve üstün kişilik özelliklerini tercih etmişlerdir.Anahtar Sözcükler: Kaside, Övme, Övünme

Kasida, in classical Turkish literature, is a type of poem which has mostly been preffered by poets in order to praise some distinguished figures. On this study, praise and self-praise couplets have been looked through from the kasidas of Fehîm-i Kadîm, Nâilî-i Kadîm, Neşâtî, Şehrî and Şeyh Gâlib who are the well-known poets from the era of classical Turkish literature which is known with the name of ?Sebk-i Hindî?. Couplets have been categorized according to praised figures and generally comparison has been made. The purpose is to determine in details how the poets above- mentioned did the praise and self- praise and who did they praise.On our study, it has generally been succeeded and been brought out who and how did the poets praise after having analyzed and distributed. The poets have generally praised the figures who would protect them physically and spiritually correctly to the political and culturel atmosphere of the Ottoman Empire. They have firstly praised the emperors (sultans) and high-ranking statesmen and then the sheikhs (leaders) of the tariqahs (religious group) of which they have been the member or the distinguished figures in Islamic religion such as Hz. Ali, Hz. Ebubekir, Hz. Huseyin and so on.While doing self praise, they have generally preferred mentioning teir own preeminent personality features and superiorities against the other poets.Key Words: Kasida, Praise, Self Praise
According to poets of Sebk-i Hindî (Nâilî, Neşâtî, Fehîm, Şehrî and Şeyh Gâlib) praise and self praise in kasidas
Keywords: Türk Dili ve Edebiyatı